Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/srep41528
|View full text |Cite
|
Sign up to set email alerts
|

The hypothalamic NPVF circuit modulates ventral raphe activity during nociception

Abstract: RFamide neuropeptide VF (NPVF) is expressed by neurons in the hypothalamus and has been implicated in nociception, but the circuit mechanisms remain unexplored. Here, we studied the structural and functional connections from NPVF neurons to downstream targets in the context of nociception, using novel transgenic lines, optogenetics, and calcium imaging in behaving larval zebrafish. We found a specific projection from NPVF neurons to serotonergic neurons in the ventral raphe nucleus (vRN). We showed NPVF neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
4
17
1
Order By: Relevance
“…In mammalian brains, npvf is highly enriched in the dorsomedial hypothalamus ( Hinuma et al, 2000 ; Liu et al, 2001 ; Ubuka et al, 2009 ). Similarly, using ISH we found that npvf is exclusively expressed in the zebrafish dorsomedial hypothalamus at 5 days post-fertilization (dpf) ( Figure 5A–C ), similar to previous observations ( Madelaine et al, 2017 ; Yelin-Bekerman et al, 2015 ). However, zebrafish larvae only have ~15 NPVF neurons per brain hemisphere, over an order of magnitude fewer than the number of NPVF neurons in mice ( Poling et al, 2012 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In mammalian brains, npvf is highly enriched in the dorsomedial hypothalamus ( Hinuma et al, 2000 ; Liu et al, 2001 ; Ubuka et al, 2009 ). Similarly, using ISH we found that npvf is exclusively expressed in the zebrafish dorsomedial hypothalamus at 5 days post-fertilization (dpf) ( Figure 5A–C ), similar to previous observations ( Madelaine et al, 2017 ; Yelin-Bekerman et al, 2015 ). However, zebrafish larvae only have ~15 NPVF neurons per brain hemisphere, over an order of magnitude fewer than the number of NPVF neurons in mice ( Poling et al, 2012 ).…”
Section: Resultssupporting
confidence: 91%
“…We further identified a 4 kb genomic region directly 5’ to the npvf open reading frame that is sufficient to drive expression of enhanced green fluorescent protein (EGFP) specifically in npvf -expressing neurons, with 98 ± 1% (n = 12) of EGFP positive cells expressing npvf mRNA, and 97 ± 1% (n = 12) of npvf -positive cells expressing EGFP ( Figure 5B and C , Table 1 ). This neuronal population sends dense projections within the hypothalamus and to the raphe nuclei of the hindbrain ( Madelaine et al, 2017 ), and sparse projections to the forebrain, tectum, and spinal cord ( Figure 5—figure supplement 1 ), suggesting that it may regulate neurons in these regions ( Madelaine et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest that there are at least two functionally distinct neuronal populations among tph2 -expressing IRa neurons, consistent with studies of the mammalian RN that identified molecularly distinct sub-populations with distinct efferent projection patterns and functions (Huang et al, 2019; Ren et al, 2018; Ren et al, 2019). The NPVF neuron-induced inhibition of a sub-population of IRa neurons that we observed is consistent with a previous study which reported that optogenetic stimulation of NPVF neurons resulted in decreased GCaMP6s fluorescence in IRa neurons (Madelaine et al, 2017), although the effect was small and slow compared to our data. Further studies are needed to explore the molecular and functional diversity of RN neurons in zebrafish.…”
Section: Discussionsupporting
confidence: 93%
“…Overexpression of npvf or stimulation of npvf -expressing neurons results in increased sleep, whereas pharmacological inhibition of NPVF signaling or ablation of npvf -expressing neurons results in reduced sleep (Lee et al, 2017). While it is unknown how the NPVF system promotes sleep, these neurons densely innervate a region of the hindbrain that is consistent with the location of the RN (Lee et al, 2017; Madelaine et al, 2017). Because perturbations of the NPVF system and RN have similar effects on sleep, and processes of npvf -expressing neurons are found near the RN, we hypothesized that the NPVF system promotes sleep via the RN.…”
Section: Introductionmentioning
confidence: 81%
“…The pixels containing the fish tail were determined in each frame of the tail monitoring videos using adaptive thresholding and blob detection algorithms in Scikit-image (van der Walt et al, 2014; Madelaine et al, 2017). Tail movements were identified by analyzing the number of tail-containing pixels that did not overlap between adjacent frames.…”
Section: Methodsmentioning
confidence: 99%